Near-Infrared Spectroscopy Screening to Allow Detection of Pathogenic Mitochondrial DNA Variants in Individuals with Unexplained Abnormal Fatigue: A Preliminary Study. Issue 5 (May 2018) - Celie, Bert M.; Mariman, An; Boone, Jan; Delesie, Liesbeth; Tobback, Els; Seneca, Sara; De Paepe, Boel; Vogelaers, Dirk; Van Coster, Rudy N.; Bourgois, Jan G.
Unexplained abnormal fatigue is characterized by chronic fatigue persisting for at least six months and not sufficiently explained by any recognized medical condition. In this pilot study, twelve individuals with abnormal fatigue remaining unexplained after thorough screening were investigated using a near-infrared (NIR) spectroscopy handgrip test. Four of them were found to have an abnormal oxygen extraction pattern similar to participants with documented mitochondrial myopathy. In three of the four individuals, diverse mitochondrial abnormalities were documented by spectrophotometric, immunocytological, fluorescent, and morphological analyses performed in skeletal muscle and in cultured skin fibroblasts. Three of the four participants with decreased muscular oxygen extraction were each shown to harbor a different homoplasmic pathogenic mitochondrial DNA point mutation (m.961T > C, m.1555A > G, m.14484T > C). In the fourth participant, the presence of multiple large mitochondrial DNA deletions was suspected in muscle tissue. In contrast, none of the eight abnormally fatigued participants with normal NIR spectroscopy results harbored either a pathogenic mitochondrial DNA point mutation or large deletions ( P  < 0.001). This pilot study shows that NIR spectroscopy may serve as a noninvasive screening tool to delineate a subgroup (of participants) with mitochondrial dysfunction among the large group of individuals with unexplained abnormal fatigue.